Teachers’ beliefs about oral corrective feedback: a comparison of secondary and adult education - Roothooft, Hanne (Huarte de San Juan. Filología y Didáctica de la Lengua, 2018)
Although there is a large number of studies showing the effectiveness of oral corrective feedback (CF) for second language acquisition, it is not clear to what extent teachers believe in its usefulness. A few survey studies have found that students want to be corrected much more than their teachers believe to be desirable. However, other aspects of oral CF, such as CF-types and timing, have hardly received any attention in those studies. Therefore, the present study compares the views of private language school and secondary school EFL teachers about questions such as: how to correct students, when to correct them and what types of errors to correct. Despite the difference in teaching context, both groups of teachers largely agreed that CF is important, but that too many corrections might interfere with fluency development and students’ confidence. Most of the teachers also seemed to prefer more implicit types of CF. These findings point to the need for more teacher training on oral CF.